Women, peace, and security : feminist perspectives on international security - Leprince, Caroline; Steer, Cassandra (Human dimensions in foreign policy, military studies, and security studies, 2021)
"Greater participation by women in peace negotiations, policy-making and legal decision-making would have a lasting impact on conflict resolution, development, and the maintenance of peace in post-conflict zones. Women, Peace, and Security lays the groundwork for this enhanced participation, drawing from insightful research by women scholars and applying a feminist lens to contemporary security issues. This timely collection of essays promotes the adoption of a feminist framework for international security issues and presents the voices of some of the most inspiring thinkers in feminist international relations in Canada. Women, Peace, and Security provides insightful recommendations to researchers conducting fieldwork, and methodological insights on how to develop feminist research design in international relations and how to adopt feminist ethical considerations. Contributions include gender-based analyses of the challenges faced by the Canadian military and by families of serving members. From Canada's Famous Five to the women's marches of 2017, lessons are drawn to inform new generations of women activists, concluding with a clarion call for greater allyship with Indigenous women and girls to support decolonization efforts in Canada. Offering a unique range of perspectives, narratives, and contributions to international relations and international law, this volume brings women's voices to the forefront of vital conversations about fundamental peace and security challenges."--